An Examination of the Relationship between Perceived price Fairness on Customer Satisfaction and Loyalty in Kenyan Star-Rated Restaurants (International Journal of Scientific Research and Management (IJSRM), 2018)
Perceived price fairness is an important predictor of relationship quality, trust, satisfaction and loyalty of customers visiting restaurants. Although several studies on customer satisfaction and loyalty have been done, little is still known about customer satisfaction and loyalty regarding perceived price fairness in Kenyan rated restaurants. The main objective of the study was therefore to examine the relationship between perceived price fairness on customers’ satisfaction and loyalty at rated restaurants in Nairobi and Coastal region. A cross sectional survey study was used in recording the information that is present in the population. Simple random sampling method was used in selecting 345 customers used in the study. The target population included all customers visiting the selected restaurants. Structured questionnaires were used in acquiring relevant information from customers. Descriptive statistics and inferential statistics (linear regression analysis) were used in analyzing the objective. The results indicated significant relationship between perceived price with satisfaction and return intention (p< 0.05), leading to the rejection of the hypotheses. Majority of the customers were found to be satisfied with all dimensions of perceived price which implied that satisfaction of perceived price fairness led to return intention of customers in the rated restaurants. The study suggested that the restaurant managers should improve on both perceived value and price. They should also ensure that the set prices are not more than the prices of their competitors of the same standard. Investment on staff training was also suggested.